Balancing antimicrobial performance with hemocompatibility in amphiphilic homopolymers - Zhu, Zhiyuan; Jeong, Gookyeong; Kim, Seung-Jin; Gadwal, Ikhlas; Choe, Youngson; Bang, Joona; Oh, Min-Kyu; Khan, Anzar; Rao, Jingyi (Journal of Polymer Science Part A- Polymer Chemistry, 2018)
This work establishes amphiphilic polymethacrylates as new antimicrobial candidates that can be synthesized through a combination of controlled free radical polymerization and sequential postpolymerization modification protocols. When conjugated with a polyethylene glycol segment, the block copolymers exhibit a balanced performance between high antibacterial activity and high hemocompatibility.